2005
DOI: 10.1080/01650250444000432
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in infant attention skills, joint attention, and emotion regulation behaviour

Abstract: This study examined the concurrent and predictive relations between infant attention skills, joint attention, and emotion regulation. Infants' gaze following skills and duration of orienting were assessed at 6 months of age, and collaborative joint attention and emotion regulation skills were assessed at 24 months of age. The results indicated that infants' ability to follow direction of gaze at 6 months was significantly correlated with emotion regulation strategy use at 24 months of age, and that collaborati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
67
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 26 publications
1
67
0
3
Order By: Relevance
“…In turn, high duration of orienting could be seen as an infant strategy to manage possibly passive parenting behavior (Morales, Mundy, Crowson, Neal, & Delgado, 2005). This is in line with the findings of family dysfunction (King & Mallinckrodt, 2000) and especially low family expressiveness (e.g.…”
mentioning
confidence: 71%
“…In turn, high duration of orienting could be seen as an infant strategy to manage possibly passive parenting behavior (Morales, Mundy, Crowson, Neal, & Delgado, 2005). This is in line with the findings of family dysfunction (King & Mallinckrodt, 2000) and especially low family expressiveness (e.g.…”
mentioning
confidence: 71%
“…For example, poor attentional control is associated with increased emotional arousal to stressors (Rothbart, Posner, & Boylan, 1990;Rothbart, Ziaie, & O'Boyle, 1992) and decreased abilities to down-regulate affective arousal (Morales, Mundy, Crowson, Neal, & Delgado, 2005;Posner & Rothbart, 1998). Research has also shown that, among highly anxious children, attentional focus (i.e., the ability to concentrate and focus attention on one task) and attentional shifting (i.e., the ability to engage in dual tasks and shift attention from one task to another) predicted severity of trait anxiety above and beyond neuroticism (Muris, de Jong, & Engelen, 2004).…”
Section: Introductionsmentioning
confidence: 98%
“…Infants use non-verbal joint attention as a means of engaging in social interactions with peers and infant teachers (Dunham & Moore, 1995;Liszkowski, Carpenter, Henning, Striano, & Tomasello, 2004;Morales et al, 2005). Joint attention is an important precursor to the development of understanding others' emotions, intentions, and beliefs, and is viewed as an essential component to establishing synchronous relationships.…”
mentioning
confidence: 98%
“…Studies of joint attention, the process by which infants and adults have a common or shared focus on an object or activity, have shown this phenomenon to be a foundational element to language development, socio-cognitive development, and social understanding (Morales, Mundy, Crowson, Neal, & Delgado, 2005;Wittmer & Petersen, 2010). Infants use non-verbal joint attention as a means of engaging in social interactions with peers and infant teachers (Dunham & Moore, 1995;Liszkowski, Carpenter, Henning, Striano, & Tomasello, 2004;Morales et al, 2005).…”
mentioning
confidence: 98%